A Novel Digital Technique for Measuring the Accuracy of an Indirect Bonding Technique Using Fixed Buccal Multibracket Appliances - Faus Matoses, Ignacio; Guinot Barona, Clara; Zubizarreta Macho, Álvaro; Paredes Gallardo, Vanessa; Faus Matoses, Vicente (My University, 2021)
The aim of this study was to analyze the accuracy and predictability of the indirect bonding technique of fixed buccal multibracket appliances using a customized iterative closest point algorithm. Materials and Methods: A total of 340 fixed buccal multibracket appliances were virtually planned and bonded on 34 experimental anatomically based acrylic resin models by using orthodontic templates designed and manufactured to indirectly bond the fixed buccal multibracket appliances. Afterwards, the models were submitted to a three-dimensional impression technique by an intraoral scanner, and the standard tessellation language digital files from the virtual planning and the digital impression were aligned, segmented, and realigned using morphometric software. Linear positioning deviations (mm) of the fixed buccal multibracket appliances were quantified at mesio-distal, bucco-lingual/palatal, and gingival/occlusal (vertical) planes, and angular deviations ( ¿ ) were also recorded by analyzing the torque, tip, and rotation using a customized iterative closest point algorithm, the script for which allowed for an accuracy measurement procedure by comparing the tessellation network positioning of both standard tessellation language digital files. Results: The mean mesio-distal deviation was ¿0.065 ± 0.081 mm, the mean bucco-lingual/palatal deviation was 0.129 ± 0.06 m, the mean vertical deviation was ¿0.094 ± 0.147 mm, the mean torque deviation was ¿0.826 ± 1.721¿ , the mean tip deviation was ¿0.271 ± 0.920¿ , and the mean rotation deviation was ¿0.707 ± 0.648¿ . Conclusion: The indirect bonding technique provides accurate and predictable positioning of fixed buccal multibracket appliances.
Keywords: orthodontics; digital; morphometry; accuracy; indirect bonding